Examining Factors that Affect the Quality of Government Financial Statements - Kartim, Kartim (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This study evaluates the impact of apparatus competence, financial information system utilization, auditor quality, and auditor opinion on the credibility of government financial statements. Research Design and Methodology: A quantitative approach was employed using primary data from questionnaires distributed to 60 respondents, including the Financial Report Compilation Team and external auditors from the Supreme Audit Agency (BPK), selected through purposive sampling. Data analysis involved descriptive statistics, normality tests, multicollinearity and heteroscedasticity tests, multiple regression analysis, R-squared tests, t-tests, and F-tests. Findings and Discussion: The findings show a significant positive relationship between the quality of financial statements the Jayapura Regional Government produced and the four factors examined. Apparatus competence enhances accuracy and compliance, while financial information systems improve efficiency and transparency. Auditor quality strengthens financial reporting reliability, and favorable audit opinions reflect sound financial management practices. Implications: The study suggests that enhancing personnel competence, optimizing financial information systems, and ensuring high auditor quality are crucial for improving financial statement credibility. Local governments should prioritize recruitment, continuous training, and practical financial reporting technologies to promote greater accountability and transparency.